2020
DOI: 10.1021/acs.jpclett.0c01615
|View full text |Cite
|
Sign up to set email alerts
|

Multiquantum Counting of Trityl Radicals

Abstract: We demonstrate a series of multitrityl radical compounds where accurate spin-counting by pulsed electron paramagnetic resonance (EPR) can be achieved at X-band (9 GHz) frequencies, even for molecules with very short and flexible linkers. Multiquantum filter experiments, well-known from NMR, were used to count the number of coupled electron spins in these compounds. The six pulse double quantum filter sequence used in EPR for distance determinations in biradicals was used. Precise phase settings to separate hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Also, several membrane proteins form homo‐ or heterooligomeric complexes [14] and orthogonal labeling strategies would greatly facilitate their investigations. The carbon‐centered trityl radicals have attained much attention for ESR and also as an orthogonal tag with other spin labels [8, 15–22] . Like the Gd 3+ ‐based labels, they are stable in the reducing cellular environment and their narrow linewidth provides high sensitivity.…”
Section: Figurementioning
confidence: 99%
“…Also, several membrane proteins form homo‐ or heterooligomeric complexes [14] and orthogonal labeling strategies would greatly facilitate their investigations. The carbon‐centered trityl radicals have attained much attention for ESR and also as an orthogonal tag with other spin labels [8, 15–22] . Like the Gd 3+ ‐based labels, they are stable in the reducing cellular environment and their narrow linewidth provides high sensitivity.…”
Section: Figurementioning
confidence: 99%
“…With the advent of ultra-wideband EPR spectrometers as well as novel spin labels, in particular based on the trityl radical with its narrow EPR spectrum, single-frequency PDS techniques find broader applications (Kunjir et al, 2013;Schöps et al, 2015;Akhmetzyanov et al, 2015;Meyer et al, 2018;Bretschneider et al, 2020;Krumkacheva and Bagryanskaya, 2017a;Denysenkov et al, 2017). In theory, singlefrequency experiments are advantageous, particularly when applied to narrow lines, as they do not suffer from problems such as limited modulation depth due to separation into spin packets or pulse overlap leading to artefacts as known for DEER.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of ultra-wide band EPR spectrometers as well as novel spin labels, in particular based on the trityl radical with its narrow EPR spectrum, single frequency PDS techniques find broader applications (Kunjir et al, 2013;Schöps et al, 2015;Akhmetzyanov et al, 2015;Meyer et al, 2018;Bretschneider et al, 2020;Krumkacheva and Bagryanskaya, 2017a;Denysenkov et al, 2017). This necessitates reliable distance determination from SIFTER time domain data, which is severely limited by the unknown intermolecular background in the dipolar evolution data from this technique (Jeschke et al, 2000;Akhmetzyanov et al, 2015;Meyer et al, 2018;Ibáñez and Jeschke, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While significant efforts need to be made in order to garner the advantages of the SIFTER experiment for nitroxide spin labels, single-frequency experiments are the preferred choice when dealing with spin systems with more narrow line widths. One such class of systems are trityl radicals -carbon-centered organic radicals based on which numerous spin labels have been developed (Krumkacheva and Bagryanskaya, 2016;Jassoy et al, 2017;Yang et al, 2012;Fleck et al, 2021;Shevelev et al, 2018;Krumkacheva and Bagryanskaya, 2017b;Yang et al, 2016;Tormyshev et al, 2020;Ketter et al, 2021) as their high reduction stability and long decoherence times make them potentially suitable for room temperature as well as in-cell distance measurements (Reginsson et al, 2012;Jassoy et al, 2017;Yang et al, 2012). In applications using trityls it has been shown that SIFTER is significantly superior to double-frequency experiments (Meyer et al, 2018), unless when measuring at very high magnetic fields, where the line width is sufficiently increased due to its dependence on g-anisotropy and where available microwave power and bandwidth may be insufficient to enable efficient excitation in single-frequency experiments (Akhmetzyanov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%